Jaynes–Cummings model with degenerate atomic levels and two polarization modes of the quantized field. (13th March 2019) - Reshetov, V A
Abstract: The Jaynes–Cummings model describing the interaction of two polarization modes of the quantized electromagnetic field with an isolated two-level atom with the levels degenerate in the projections of the angular momenta on the quantization axis is studied. The general expression for the evolution operator for such a model is obtained. The examples of low values of the level angular momenta or single photon in the cavity are discussed.